The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0167778
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin B Receptors on Primary Chicken Müller Cells and the Human MIO-M1 Müller Cell Line Activate ERK Signaling via Transactivation of Epidermal Growth Factor Receptors

Abstract: Injury to the eye or retina triggers Müller cells, the major glia cell of the retina, to dedifferentiate and proliferate. In some species they attain retinal progenitor properties and have the capacity to generate new neurons. The epidermal growth factor receptor (EGFR) system and extracellular signal-regulated kinase (ERK) signaling are key regulators of these processes in Müller cells. The extracellular signals that modulate and control these processes are not fully understood. In this work we studied whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…In order to dissect how EDNRA signals to ERK and hence regulates cell growth, we used different kinase inhibitors and found that while a PKC inhibitor did not impact on the protective function of EDN1, inhibiting RAF kinases with RAF265 or blocking RTK activity using the pan RTK inhibitor dovitinib overcame this protection (Fig EV5H and I). This suggests a crosstalk between EDNRA and RTK signalling as it has been described previously (Harada et al , ; Harun‐Or‐Rashid et al , ; Moody et al , ), which ultimately activates ERK through RAF.…”
Section: Resultssupporting
confidence: 71%
“…In order to dissect how EDNRA signals to ERK and hence regulates cell growth, we used different kinase inhibitors and found that while a PKC inhibitor did not impact on the protective function of EDN1, inhibiting RAF kinases with RAF265 or blocking RTK activity using the pan RTK inhibitor dovitinib overcame this protection (Fig EV5H and I). This suggests a crosstalk between EDNRA and RTK signalling as it has been described previously (Harada et al , ; Harun‐Or‐Rashid et al , ; Moody et al , ), which ultimately activates ERK through RAF.…”
Section: Resultssupporting
confidence: 71%
“…This overexpression is mainly observed in the GCL where the end feet of MCs reside [ 52 ] and close to the damaged RGCs, as shown in Figure 2 and Figure 4 . Thus, it is tempting to suggest that the activation of the survival MAPK signaling pathway results in neuroprotection through activation of both MCs and RGCs, as has been described in other experimental models such as NMDA excitotoxicity [ 53 , 54 ], or retinal detachment, ischemia-reperfusion, inflammation and glaucoma (reviewed in [ 55 ]). P-MAPK and MAPK was also observed in the outer retina; however, further studies are need to understand this event.…”
Section: Discussionmentioning
confidence: 99%
“…In a variety of ways, RTK signaling can require mediation by G protein coupled receptors, a mechanisms called transactivation (Kilpatrick & Hill, 2021). Prior in vitro explant studies have implicated a convergence of Ret and Ednrb at the level of protein kinase A activity ( (Barlow et al, 2003;Goto et al, 2013); see also Discussion), although other mechanisms of transactivation have been described for Ednrb to other RTKs (Grantcharova et al, 2006;Harun-Or-Rashid, Konjusha, Galindo-Romero, & Hallbook, 2016), and Ret with other GPCRs (Tsuchioka, Takebayashi, Hisaoka, Maeda, & Nakata, 2008). Because Ret expression was preserved in Wnt1Cre-derived enteric progenitors even as they were nonresponsive to GDNF, we considered that transactivation via Ednrb might be involved.…”
Section: Ret Is Required For Pax2cre-derived Ens Progenitor Cells Mig...mentioning
confidence: 99%